Synthesis of imidazole-activated ribonucleotides using cyanogen chloride. Issue 5 (21st December 2017) - Yi, Ruiqin; Hongo, Yayoi; Fahrenbach, Albert C.
Abstract : Just add cyanide and bleach! Aqueous cyanide anion, hypochlorous acid, imidazole and ribonucleoside 5′-monophosphate furnish in one-pot the chemically activated 5′-phosphorimidazolides. Abstract : We report the syntheses of ribonucleoside 5′-monophosphates activated with imidazole, using a mechanism which relies on the in situ generation of cyanogen chloride from the reaction of cyanide anion with hypochlorous acid. Cyanogen chloride reacts rapidly with imidazole to form diimidazole imine as the major product, a species which affords the activation of ribonucleoside 5′-monophosphates to their 5′-phosphorimidazolides.